ASPEK PSIKOLOGIS DALAM PENGAMBILAN KEPUTUSAN KEUANGAN - asjari, fachrudy (Majalah Ekonomi, 2017)
Financial decision making is an important aspect in the life of the company as well as private. This decision not only depends on the intellectual ability but also psychological abilities. The proper decision making requires tranquility psychologically and mental maturity of a person. This research intended to analyze the psychology aspect and finance desicion making. Finance desicion making was facilitated by Psychology aspect. Investors as individual and institutional settings conducive to the development of high level of organizational capital. The research by utilizing literature study to analyze variables. Financial decision making and psychological abilities needs a few variables to support them get the goals. These variables in this study revealed which needed by companies. The results of this research were empirical date of the development of the theoretical of human resources, behavior finance and practical in management. Key words: Psychological Aspect and Financial Decision